EVALUASI PROGRAM EKSTRAKURIKULER CODING DI SD PANGUDI LUHUR AMBARAWA MENGGUNAKAN MODEL DISCREPANCY EVALUATION - Putri, Gabriela Hemas Swasti Kirana; Mawardi (Universitas Negeri Medan, 2025)
This study evaluates the extracurricular coding program at SD Pangudi Luhur Ambarawa using the Discrepancy Evaluation model, to see the level of gap between the standards and objectivies that have been set and the implementation of the program, which includes five aspects: design, installation, process, product, and cost-benefit. Coding is becoming an increasingly important skill in the digital era, so it is introduced in extracurricular activities to improve understanding of programming concepts, creativity, and structured logical thinking skills. This study used quantitative and qualitative approaches woth evaluation methods. Data were collected through questionnaires, interviews, observations, and document studies with research subjects including principals, teachers, coordinators, extracurricular assistants, coding tutors, and students. The data analysis technique used was the Miles and Huberman model which includes data collection, data reduction, data display, and conclusion drawing. The evaluation results show that the extracurricular coding program has been running in accordance with predetermined standards with a very low level of gap or discrepancy in each aspect analyzed. Nevertheless, there are still some obstacles in its implementation, such as the delay of some students in completing the coding project and technical technical constraints related to facilities and infrastructure. However, the program is still considered to provide significant benefits for both students and schools in improving 21st century skills in technology. Therefore, the coding extracurricular program at SD Pangudi Luhur Ambarawa is recommended to be further developed with improved facilities and more optimal learning strategies. This study evaluates the extracurricular coding program at SD Pangudi Luhur Ambarawa using the Discrepancy Evaluation model, to see the level of gap between the standards and objectivies that have been set and the implementation of the program, which includes five aspects: design, installation, process, product, and cost-benefit. Coding is becoming an increasingly important skill in the digital era, so it is introduced in extracurricular activities to improve understanding of programming concepts, creativity, and structured logical thinking skills. This study used quantitative and qualitative approaches woth evaluation methods. Data were collected through questionnaires, interviews, observations, and document studies with research subjects including principals, teachers, coordinators, extracurricular assistants, coding tutors, and students. The data analysis technique used was the Miles and Huberman model which includes data collection, data reduction, data display, and conclusion drawing. The evaluation results show that the extracurricular coding program has been running in accordance with predetermined standards with a very low level of gap or discrepancy in each aspect analyzed. Nevertheless, there are still some obstacles in its implementation, such as the delay of some students in completing the coding project and technical technical constraints related to facilities and infrastructure. However, the program is still considered to provide significant benefits for both students and schools in improving 21st century skills in technology. Therefore, the coding extracurricular program at SD Pangudi Luhur Ambarawa is recommended to be further developed with improved facilities and more optimal learning strategies.